Avaliação do acesso e uso de um serviço de reabilitação física de referência estadual em Mato Grosso - Lima, Adriana Maria Silva (2023)
Access is a priority dimension for the quality of the health system, enabling a population to use health services according to their existing needs. In rehabilitation services, access enables the development of functional capabilities and independence of people with disabilities (PWD) for social participation, and must be ensured in accordance with the principles of the Unified Health System. Objective – To evaluate access and use of a state reference physical rehabilitation service located in the city of Cuiabá-MT. Method – Health evaluation research, of the case study type, with qualitative and quantitative approaches, carried out in a Specialized Rehabilitation Center (CER), through the collection of primary and secondary data analyzed according to the Behavioral Model of the Use of Health Services. Secondary data were collected by consulting public databases and legal documents (contextualization of the Baixada Cuiabana Health Region, in which the rehabilitation service under study is located) and by extracting data from 196 medical records of adult users, searching for physical rehabilitation in the CER reception sector (quantitative approach for the demographic and socioeconomic characterization of users who sought the physical rehabilitation service). The primary data comprised 22 interviews with the management team and health professionals (qualitative approach) and 51 interviews with adult users of the CER's physical rehabilitation sector (quantitative approach) to analyze perceptions about the context of the Personal Care Network with Disabilities in Baixada Cuiabana (RCPD), the structure and organization of the service, access, use and users' perception of satisfaction with the physical rehabilitation service. Statistical analysis of quantitative data was performed using Stata Software version 16.0. Qualitative data from interviews with the management team and health professionals were analyzed using Content Analysis. Results – The contextual analysis of the RCPD identified difficulties in the structure and organization, mainly regarding the agreement of inter-management services and the absence of a regulatory system for specialized rehabilitation services. Regarding the individual characteristics of the rehabilitation service under study, the difficulties were related to the physical structure, insufficient human resources and the organization of work processes. Among users who sought and used the service, the influence of disability on the users' socioeconomic situation was verified. As potential, the qualified service of the rehabilitation team stood out and, as obstacles, the lack of health transport and the unavailability of vacancies. Such findings suggested the fragility of the RCPD, with flaws in the comprehensiveness of health care, compromising access to services in a timely manner to meet the health needs presented by physical PWD. Conclusions – The results of the study indicated the urgent need to review the planning, structuring and organization of the RCPD to increase access for people with physical disabilities to the various points of care, as the challenges are not restricted to the difficulties inherent to the service in study, but involve the effective implementation of this Network. To this end, it is recommended that CRIDAC regain political protagonism in planning the RCPD, with the strengthening and support of the State Conducting Group.